Itaconate Suppresses Formation of Neutrophil Extracellular Traps (NETs): Involvement of Hypoxia-Inducible Factor 1α (Hif-1α) and Heme Oxygenase (HO-1) - Burczyk, Gabriela; Cichon, Iwona; Kolaczkowska, Elzbieta (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) immobilize pathogens during early stages of systemic inflammation but as the reaction progresses they become detrimental to endothelial cells and the organ-specific cells. For this reason it would be of importance to control their formation by either physiological or pharmacological means. Endogenously, formation of NETs is under control of cellular and whole organism metabolism as shown previously in the course of bacterial systemic inflammation, obesity or the combination of the two. Numerous leukocytes are subjected to immunometabolic regulation and in macrophages exposure to lipopolysaccharide (LPS) leads to two breaks in the Krebs cycle that impact this cell functioning. As a consequence of the first break, anti-microbial itaconic acid (itaconate) is produced whereas the second break activates hypoxia-inducible factor-1α (HIF1-α). In turn, itaconate activates transcription of the anti-inflammatory nuclear factor erythroid 2-related factor 2 (Nrf2) which upregulates cyto-protective heme oxygenase (HO-1). Here we report that exogenously added derivative of the itaconic acid, 4-octyl itaconate (4-OI), diminishes formation of NETs by neutrophils of either normal (lean) or obese mice, and independently of the age of the animals or immunoaging. Elucidating the mechanism of this inhibition we unravel that although Nrf2/HO-1 expression itself is not altered by 4-OI, it is up-regulated when compared against the NET formation while HIF1-α is downregulated in 4-OI-pretreated LPS-stimulated neutrophils in either way. We further show that blockage of HIF1-α by its specific inhibitor diminishes NET release as does inhibition by 4-OI. Also inhibition of HO-1 activity correlates with diminished LPS-induced NET release upon pre-treatment with 4-OI albeit LPS alone induced NETs are not HO-1-dependent. In summary, we unravel that 4-OI inhibits NET formation by murine neutrophils independently of their origin (health vs. metabolically challenged animals) and the age of individuals/immunosenescence via inhibition of HIF1-α and induction of HO-1.